Educational System in Baron Stieglitz Central College for Technical Drawing during the Directorship of M. Mesmakher - Dobina, Anastasia O. (Actual Problems of Theory and History of Art, 2014)
The creation of the Central College for Technical Drawing marked a new step in the development of artistic education in Russia, taking into account new challenges put forward by the industry. This research is devoted to the formative period of this educational institution, from the year of Baron Stiglitz’donation (1876) and the directorship of Maksmillian Mesmakher (1876–1896).The activities of academic M. Mesmakher as the Director of the College for Technical Drawing had direct influence on the methods of teaching. Yet, Mesmakher remained a controversial figure in his circle. Patrons of art and members of the College Council treated him with respect and appreciated his advices. He was a successful architect, and his students participated in many of his works. He also was one of professors in theory and history of styles. The situation changed in 1890’s: many artists started to doubt the need of academic professors for teaching in an industrial College.The period of Mesmakher’s directorship was only the first step in shaping the educational system of the College. Further changes of teaching methods are studied insuffi ciently and need a thorough research using the archival data and comparison with the educational systems in similar colleges in Europe.
Keywords: Arts and crafts education; art education applied to industry; applied arts; M. Mesmakher